(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: The present systematic study delves into the dynamic environment of healthcare technology adoption in the distinct setting of Saudi Arabian nursing practice. Understanding how advances in telemedicine, digital health technologies, and patient engagement techniques affect patient outcomes and nursing care delivery is becoming more and more important. In light of the fast evolving healthcare system, which is marked by a rise in digitization and technological innovation, the goal of this study is to offer a thorough evaluation of the present state of knowledge and suggest areas for additional research and development. Aim: To examine the influence of emerging technologies on nursing and patient’s outcomes. Method: A thorough search of databases, including Scopus, PsycINFO, and Web of Science, was conducted in order to categorize relevant research that was published between 2020 and 2023. The inclusion criteria for this research were English-language papers that focused on examining influence of emerging technologies on nursing practices and patents outcomes. The selected studies also have to offer useful information on team dynamics and employ recognized measurement scales. Following an initial screening and quality evaluation, eleven studies were included in the synthesis. Results: The study database was searched through electronic databases, identifying 331 records. 14 unique records were assessed for eligibility based on titles and abstracts. After initial screening, 11 studies were selected for full-text assessment. After independent review, 11 studies met criteria and were included in the systematic review. The selected studies were conducted between 2020-2023 and varied in design. The PRISMA flowchart illustrates the selection process. Quality evaluation involves peer-reviewed journals, overall assessment, and quality management. Conclusion: The review of studies reveals that technology, including telemedicine and digital health tools, positively impacts nursing practice and patient outcomes in Saudi Arabia. Despite challenges like staffing shortages and regulatory compliance, sustained funding and collaboration among policymakers, healthcare leaders, educators, and technology developers are essential to fully leverage these advancements for improved patient care.